Strengthening the sustainability of European food chains through quality and procurement policies. (February 2022) - Mattas, K.; Tsakiridou, E.; Karelakis, C.; Lazaridou, D.; Gorton, M.; Filipović, J.; Hubbard, C.; Saidi, M.; Stojkovic, D.; Tocco, B.; Tregear, A.; Veneziani, M.
Abstract: Background: The nexus of agri-food and sustainability in economic development has recently attracted the interest of policymakers, as global challenges like climate change and food security are revisited and reassessed. The critical role of food production in economic development has been emphasized through targeted agricultural quality policies. Many developed countries worldwide, including EU member states, have introduced food quality policies that could support sustainability. Scope and approach: This paper combines knowledge obtained by several groups in a broad EU study and the reflections on policy-related results by EU-stakeholders, streamlined by a Delphi analysis. Current work presents research-based policy recommendations and statements on various quality schemes, introductory inferred from expert opinions throughout Europe, gauged through a modified policy Delphi framework. Key findings and conclusions: A roadmap of policy and practical proposals have been identified for all key stakeholders involved in these initiatives, implying the need to reshape the supply chain dynamics to continuously improve producers, processors, retailers, and consumers within the EU and definitively worldwide. Furthermore, implementing a holistic approach considering environmental and socio-economic features can improve the effectiveness of EU food quality policies. Highlights: Research-based results using various approaches and targeting all Food Supply Chains are synthesized and emerged. Policy-related recommendations extracted directly and indirectly from a pool of synthesized results. Policy-related results to contributing to the overall sustainability of food systems has identified. Food quality schemes will be enhanced by employing policy recommendations discussed in a stakeholders participatory process (Delphi framework).